When millennials take over: preparing for the ridiculously optimistic future of business - Notter, Jamie; Grant, Maddie (S.l., 2015)
"Is your organization ready for what is coming? Between the decline of modern management, the social media shift of power toward individuals, and the ascent of the Millennial generation into leadership roles, companies of all shapes and sizes are facing a future that they are ill-equipped to handle. As a result of this perfect storm of changes, many organizations are struggling to stay relevant to customers, capitalize on opportunities in the marketplace, and attract top talent. Successful companies, on the other hand, are shifting to embrace four key capacities that will drive the future of business: digital, clear, fluid, and fast. Drawing on both cutting-edge case studies and research on Millennials in the workplace, you ll learn how to successfully apply these four capacities in your context to drive real business results, like more engaged employees, higher-value customers, greater strategic agility, and stronger, magnetic cultures. When Millennials Take Over delivers concrete, actionable advice you can use to set your company apart as a leader--rather than a follower. The only constant is change. These four capacities are the key to being able to keep up with the complexity, uncertainty and rapid shifts in our industries and our world. When Millennials Take Over is an intelligently practical guide to how you can build these capacities for your organization - starting NOW."